Etika Auditor sebagai Pemoderasi Fee Audit, Independensi, dan Kompetensi terhadap Kualitas Audit - Amadea Devota; Hero Priono (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The objective of this research is to test and analyze the impact of the audit fee, independency, and competency on audit quality with ethics of auditor as moderation variable of Public Accountant Firm in Surabaya. The sample used in the research as many as 10 Public Accountant Firms which are represented by 46 people of auditors and selected by convenience sampling method. Questionnaires is used as the primary data of this research, distributed right to the auditors in the Public Accountant Firms in Surabaya City that are used as research sample. The data analysis technique used Structural Equation Model (SEM) based Partial Least Square Analysis (PLS). The results in this research showed that (1) audit fee had positive and significant influence on audit quality, (2) independency had negative and significant influence on audit quality, (3) competency had positive and significant influence on quality audit, (4) ethics of auditor could moderate the influence on audit fee of quality audit, (5) ethics of auditor couldn’t moderate the influence on independency of quality audit, and (6) ethics of auditor could moderate the influence on competency of quality audit.